A new concept design of a motorbike with 3D model for the Malaysian market - Faris, Waleed Fekry; Al-Omari, Yasir; Sapian, Abdul Razak; Husin, Muhammad (inderscience publisher, 2011)
Although motorbikes are used widely in Malaysia, there are no published studies concerning the Malaysian user satisfaction of the current designs available and also their feedback on the ergonomics of the current designs. In this study, a survey has been done covering both styling and ergonomic aspects of the Malaysian users. The data was obtained firstly through a questionnaire to investigate the discomfort positions of the motorbikes driving for the Malaysian users and their aesthetic trends in the design in the form of shape and colours as elements of the new concept motorbike design according to their three different ethnicities namely Malay, Chinese and Indian. Also, an anthropometric and ergonomic study was used to choose the best position suited for the Malaysian users. The data collected were analysed to get the result which was considered in the final 3D model. These results were used to build the prototype with industrial clay.